ATIVISMO JUDICIAL E JUDICIALIZAÇÃO: ENTRE A DEMOCRACIA E OS DIREITOS FUNDAMENTAIS - Thiago André Silva Gonçalves (2023)
This research aims to analyze the differences between activism and judicialization of policies and their relationship with democracy and fundamental rights. The guiding problem of the research can be defined through two pillar questions: (i) are there differences between the practice of judicial activism and judicialization? and (ii) how do these postures influence democracy and fundamental rights? Incidentally, other questions arise: fulfilling the fundamental rights expressed in the Federal Constitution, through the process of judicialization, does it mean flowing into judicial activism? For this, it was necessary to understand the resizing of the constitutional jurisdiction after the Second World War and what its role in the realization of human rights. On the other hand, it studies how the process of judicial activism causes fissures in the representative system, insofar as it adopts a voluntarist attitude towards the legislation, disrespecting the semantic limits of the normative text. It is concluded that in peripheral countries, as is the case of Brazil, there must be a constitutional jurisdiction that does not fall into decisionism, but at the same time implements rights. In order to achieve a satisfactory result, bibliographical and documentary methodology was used, starting from the hypothetical-deductive method.